The structural and functional studies of the non-stereospecific α-haloacid dehalogenase (DehE) from rhizobium sp. RC1 - Abdul Hamid, Azzmer Azzar; Wong , Ee Lin; Joyce-Tan, Kwee Hong; Shamsir, Mohd Shahir; Tengku Abdul Hamid, Tengku Haziyamin; Huyop, Fahrul Zaman (2013)
Environmental pollution caused by the abundance of xenobi otic compounds in nature. For instance, synthetically halogenated compounds released from chemical industry we re proven harmful to our health and environment. However, α-haloacid dehalogenases could catalysed the removal of halides from organic haloalkanoic acids and of interest for bioremediation. This study presents the first structural conformations and important residues of the non-stereospecific α-haloacid dehalogenase, DehE from Rhizobium sp. RC1. The enzyme was modeled using ‘in silico’technique and crystal structure of DehI from Pseudomonas putida PP3 was used as a template since both of them gets high similiarity to each other. DehE consis ts of only helices motif and depicted active site showed that the binding orientiations of both D- and L-2-chlor opropionic acid by using substrate-docking analysis shared similar key binding residues among non-stereo specific α -haloacid dehalogenases. Twelve residues lining the active site has identified and some of them were verified using site-directed mutagenesis tests. Each residues was affected after mutation and Asp189 was proven to be as a catalytic residue for nucleophilic attack mechansim when its mutation resulted in total loss of activity. Three binding residues, Trp34, Phe37 and Ser188 were responsible for substrate recognition due to their mutati on had diminish activity of the enzyme to below 20%. These details will promote more protein engineering studies to α haloacid dehalogenases for future bioremediation and industrial applications.